IMF Staff Papers : Volume 1, No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1950)
This paper highlights various problems and policies related to latent inflation. Disappointment will undoubtedly be widespread if, after 10 years of inflation control, latent inflation is permitted to become active and there is a considerable rise in prices. It is not unlikely that some governments will feel they simply cannot accept such a policy. However, the prospect of wiping out or working off latent inflation in any moderate period is very slight. There is every reason to deal with the latent inflation as far as possible by absorbing it through taxation and by measures to reduce liquidity. At the same time, with increased output it should be possible to work off part of the latent inflation. Even if it becomes generally recognized that all or most of such inflation cannot be wiped out or worked off, its immediate activation may be unwise. At some stage soon, governments must face the difficulties presented by latent inflation and recognize that a comprehensive program for dealing with it must be put into effect. Unless such programs are adopted, there can be no great confidence that international payments problems can be solved simply by imposing more rigorous and more extensive controls.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet